A study on the satisfaction level among petronas user in relations with Enhancement of Standardized Work & Equipment Categories (SWEC) And Minimum Technical Requirement (MTR) / Nurulaini Bachok - Bachok, Nurulaini (Bachelor of Science (Hons) Statistics, 2015)
This project paper attempts to identify the influential factor which is participation towards enhancement of Standardized Work & Equipment Categories (SWEC) and Minimum Technical Requirement (MTR) on the satisfaction level among PETRONAS users. The response from respondents was gathered by distributing the questionnaire in the form of Microsoft Info Path file through the official email of PETRONAS. Once the respondents completely answer all the questions, they can automatically sent back the questionnaire to distributors email and the data will be automatically save in database system. The questionnaire used ten-point Likert scale to measure the dependent variable and independent variable for this study. The scales started with 1, strongly disagree and ended with scale 10, strongly agree. Furthermore, it presents and discussed causal effect of participation towards enhancement on satisfaction levels among PETRONAS users by applying statistical analysis methods of Structural Equation Modeling (SEM) that was run using and Analysis of Moment Structure Software (AMOS 18.0). The descriptive analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), non-parametric test and multiple comparison tests were used in this study to answer the objective and to prove the hypothesis in this study. This study concluded that for demographical part, organization and frequency of SWEC used variables are support for the hypothesis. In addition from multiple comparisons test conducted proved there were significant differences between paired groups of variables. Besides that, from the test for variables, dependent goal is supported for the hypothesis. Recommendation is given to improve their organization and future research for example PETRONAS should conducted training class for using the new system participated by PETRONAS users in order to increase the usage and at the same time increase the satisfaction level